Answer:
![(x-4)^2+(y-3)^2=2^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9kycod71gttrqptgoyw6u5bwf8emamn4xy.png)
Explanation:
The given circle has equation;
![x^2+y^2-8x-6y+24=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6n2r0cvwwdtk6b4fqbymf06z3qvc1yhhqi.png)
Comparing to the general equation of the circle:
![x^2+y^2+2ax+2by+c=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/e8j0ebkyshkgiesp86fp18cdmtguivajd4.png)
We have
and
![2b=-6\implies b=-3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bk61n0uqbgskzv4nl4br7xy5xupva6l2ox.png)
The center of this circle is (-a,-b)=(4,3).
The required circle has radius r=2 units.
The equation of a circle, given the center (h,k) and radius r, is given by:
![(x-h)^2+(y-k)^2=r^2](https://img.qammunity.org/2020/formulas/mathematics/high-school/kmmm139x85fjht54s8zz0668styzp2e6cm.png)
We substitute the values to obtain
![(x-4)^2+(y-3)^2=2^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9kycod71gttrqptgoyw6u5bwf8emamn4xy.png)